1987
DOI: 10.1002/polb.1987.090250912
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐enhanced raman scattering from poly(4‐vinyl pyridine)

Abstract: SynopsisSurface-enhanced Raman scattering (SERS) has been observed for poly(4-vinyl pyridine) ahsorbed onto silver island films. Bands near 1219 and 1613 c m -' , which are weak in normal Raman spectra of PVP, are strong in SEW spectra, and the band near 1020 cm-', which is the strongest band in the normal spectra, is relatively weak in SERS. The strongest bands in the SEHS spectra all belong to the same symmetry species as a z z , implying that the pyridine moieties are adsorbed through the nitrogen atoms wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…In the Raman spectrum of substituted benzimidazole, the band near 1320 and 510 cm 1 are due to out-of-plane C-H deformation, and the band at 1600 cm 1 is due to ring stretching modes. 27 The SERS spectrum in Fig. 3(B) shows an enhanced and shifted band at 510 cm 1 and a very weak band at 1600 cm 1 , indicating that the benzimidazole rings are 'lying down' flat on the surface, whereas the SERS spectrum in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the Raman spectrum of substituted benzimidazole, the band near 1320 and 510 cm 1 are due to out-of-plane C-H deformation, and the band at 1600 cm 1 is due to ring stretching modes. 27 The SERS spectrum in Fig. 3(B) shows an enhanced and shifted band at 510 cm 1 and a very weak band at 1600 cm 1 , indicating that the benzimidazole rings are 'lying down' flat on the surface, whereas the SERS spectrum in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[16,17] Commercial copper plates with a thickness of 1.5 mm were mechanically polished with a series of dry silicon carbide abrasive papers ranging from 320 to 2 000 grit. After the surface was ground, wet polishing was performed using 0.05-lm alumina powder in Microcloths (Buehler Inc.) with deionized water as the lubricant.…”
Section: Preparation Of Metal Substratesmentioning
confidence: 99%
“…[9,10] Commercial copper plates with a thickness of 1.5 mm were mechanically polished with a series of dry silicon carbide abrasive papers ranging from 320 to 2 000 grit. After the surface was grounded, wet polishing was performed using 0.05 lm alumina powder in Microcloths (Buehler Inc.) with deionized water as a lubricant.…”
Section: Preparation Of Metal Substratesmentioning
confidence: 99%
“…For example, it has been reported that the adhesion strength between polymer and metal could be enhanced significantly by incorporation of nitrogen-or oxygen-containing functionalities into the polymer. [4][5][6][7][8] Although many researchers have reported about the interfacial activity of a nitrogen-or oxygencontaining functionality onto a metal surface, [9][10][11][12] a systematic analysis on the difference in the adsorption behavior between these two functionalities onto a metal surface is still lacking.…”
Section: Introductionmentioning
confidence: 99%